Em tempos de computador e internet: um estudo sobre a implantação de uma sala de informática em uma escola pública municipal na cidade de Sapucaia/RJ - Fernandes, Paola Cordeiro (2007)
This research aims at understanding the information and technology implementation process at a district public school in Sapucaia city. Several aspects of the process have been studied such as: the main characteristics; the context underline literacy conceptions and the meanings built by the people who have participated within the whole process. An ethnographic case study has been proved to be the suitable methodological approach to this research by a number of reasons such as: the data collection techniques; the emphasis over the research process; the focus on the participant subjects meaning constructions; the possibilities to make observation of facts as they happen; the time allowed for the field work; the possibility to use a large amount of descriptive data; finally, the use of an open and flexible research design. The data analysis has taken into consideration three dimensions proposed by André (2003) to study the school daily practices: organizational; pedagogical and cultural. The results have shown that the political issues are central not only to the local educational authority, but also to the school and its participant subjects. The teacher s information and technology training leads them to a behaviorist teaching practice approach even though communication innovations have already been implemented. The information education technologies alone do not bring about changes; in order to be a useful knowledge construction tool such technologies need to be soundly incorporated within the school context. The conclusions point out that the more new information technologies are imposed over the school the more the school builds artificial mechanisms to become framed to such requirements even though inappropriate and unproductive. The arrival of information and technology in the school context examined over the research has lead to changes in the material bases for the implementation but not necessarily towards the teaching practices. The results suggest that such practices become anchored to old and traditional paradigms. Despite the fact that information devices, such as the personal computer, have become an object of desire or a sacredly fetish, the school participant subjects do not understand clearly the functions and specially the educational role of the information and technology.